Evaluation of development in supercritical water oxidation technology - Adar, Elanur; İnce, Mahir; Bilgili, Mehmet Sinan (Desalination Publ, 2019)
Supercritical water oxidation (SCWO) has been an innovative technology for the treatment of aqueous and hazardous organic wastes for 35 years. The technology provides cleaner output products and energy recovery. The purpose of this study is to evaluate the latest state of SCWO, which is an innovative and promising technology, according to the information obtained from the lab-scale, pilot-scale and full-scale applications. The process has been extensively used mostly in laboratory or pilot scale plants for model and real wastewater treatment. Industrial SCWO plants have usually closed due to corrosion, clogging and high cost problems. In order to operate this innovative technology efficiently, the main suitable wastewater should be selected, appropriate reactor design should be used, more durable materials should be produced, efficient pre-treatment should be determined so as to decrease operating costs and technical solutions should be determined. Otherwise, SCWO studies may be limited to laboratory and R&D studies.
Keywords: Supercritical water oxidation; Commercial scale; Wastewater treatment; Status; Problems